Defining a Brief Intervention for the Promotion of Psychological Well-being among Unemployed Individuals through Expert Consensus - Santos, Osvaldo; Lopes, Elisa; Virgolino, Ana; Stefanovska-Petkovska, Miodraga; Dinis, Alexandra; Ambrósio, Sara; Heitor, Maria João (Frontiers in Psychiatry, 2018)
Background: Epidemiologic evidence highlights the harmful consequences of unemployment on health and well-being. This emphasizes the need to design low-cost interventions to prevent the adverse mental health effects of unemployment. The main aim of this study was to create expert-consensus regarding development and implementation of a brief, sustainable and effective intervention program for promoting mental health among unemployed. Methods: The Delphi technique entailed a selected panel of 75 experts from various relevant professional backgrounds. Panel members were asked to state their level of agreement (5-point Likert scale) regarding (a) required characteristics for an effective mental health intervention for unemployed people and (b) key variables for assessing the effectiveness of that intervention. Consensus was obtained throughout two rounds of data collection through e-mail contact, with structured questionnaires. Items of the questionnaire were based on literature reviews about community-based interventions for unemployed individuals. Results: Overall, 46 experts collaborated with the Delphi process (final participation rate: 61.3%). Based on a review of the literature, 185 items were identified and grouped into two broad categories (set of characteristics of the intervention and set of variables for effectiveness assessment), aggregating a total of 11 dimensions. The two Delphi rounds resulted in the selection of 35 characteristic items for the intervention program and 54 variables for its effectiveness assessment. Brief group interventions were considered to be effective and sustainable for mental health promotion in unemployment conditions if targeting mental health literacy, training interpersonal skills and job-search skills. Conclusions: As agreed by the panel of experts, a brief, sustainable and effective intervention can be developed and implemented by accounting for unemployed capacity-building for mental health self-care and adequate job-searching attitudes and skills. These results should be further implemented in community and multisector-based standardized interventions, targeting mental health among unemployed people, ensuring adequate conditions for its effectiveness assessment.